Productive performance at different densities in Black Carachama (Liposarcus pardalis), a species with Amazonian aquaculture potential: Physicochemical, zootechnical and hematological parameters (Agroindustrial Science, 2025)
The aim of this study was to evaluate the zootechnical performance, macronutrient composition, physicochemical analysis of the water, and hematological parameters of the L. pardalis at different densities (5, 7, 10 fish m-2), during four-month period. A total of 660 fish were utilized in the study, with an initial mean weight of 54.89 ± 0.18 g. They were distributed across nine earthen ponds, with the number of fish allocated to each treatment as follows: T1 (150 fish), T2 (210 fish), and T3 (300 fish). The most efficacious treatment, exhibiting optimal growth, was T2 (7 fish m-2). The FW was 198.24 ± 0.69 g, and the TL was 18.2 ± 0.44 cm. These values were significantly different (p < 0.05) from those observed in the other treatments. The physicochemical parameters of the water demonstrated fluctuations at higher stocking densities. The findings demonstrate that L. pardalis modifies its lifestyle to a low metabolic capacity, resulting in alterations to the red series hematological parameters (Ht, HGB, ERIT, VCM, CHCM, HCM) in response to the increase in temperature and decrease in oxygen. Significant differences (p < 0.05) were observed between the initial and final samples. Nevertheless, this work demonstrates the importance of relating zootechnical and hematological parameters as indicators of productivity and health. Further studies are recommended on fish of the family Loricariidae to establish differences between genera, habitat, and production systems. This will facilitate the development of sustainable Amazonian aquaculture.
Keywords: Oxygen; Density; Hematology; physicochemical